Biomass pyrolysis gas conditioning over an iron-based catalyst for mild deoxygenation and hydrogen production. (1st January 2018) - Moud, Pouya H.; Kantarelis, Efthymios; Andersson, Klas J.; Engvall, Klas
Graphical abstract: Highlights: Small industrial-scale biomass pyrolysis gas conditioning over a Fe-based catalyst. No signs of deactivation during 8 h on stream. Mild deoxygenation and substantial H2 production (+1063%) was achieved. Selectivity was highest for acetic acid and methoxy phenols reduction (70–80%). A significant catalyst WGS activity was also observed. Abstract: Bio-crude is a renewable source for production of valuable energy carriers. Prior to its utilization, a conditioning step of the raw pyrolysis gas can be beneficial before the bio-crude is converted via catalytic hydrodeoxygenation (HDO) into liquid hydrocarbon products, or via steam reforming (SR) to synthesis gas/hydrogen. An experimental small industrial-scale study for the chemistry of atmospheric pressure pyrolysis gas conditioning resulting in bio-crude deoxygenation and a hydrogen-rich gas is presented and discussed. This study is performed using an iron-based catalyst without addition of hydrogen or steam. Following a short catalyst stabilization period with fluctuating bed temperatures, the catalyst operated near 450 °C at a space velocity of 1100 h −1 for 8 h under stable conditions during which no significant catalyst deactivation was observed. Experimental results indicate a 70–80% reduction of acetic acid, methoxy phenols, and catechol, and a 55–65% reduction in non-aromatic ketones, BTX, and heterocycles. Alkyl phenols and phenols were least affected, showing a 30–35% reduction. Conditioning of the pyrolysis gas resulted in a 56% and an 18 wt% increase in water and permanent (dry) gas yield, respectively, and a 29% loss of condensable carbon. A significant reduction of CO amount (−38%), and production of H2 (+1063%) and CO2 (+36%) over the catalyst was achieved, while there was no or minimal change in light hydrocarbon content. Probing the catalyst after the test, the bulk phase of the catalyst was found to be magnetite (Fe3 O4 ) and the catalyst exhibited significant water gas shift (WGS) reaction activity. The measured gas composition during the test was indicative of no or very limited Fischer-Tropsch (FT) CO/CO2 hydrogenation activity, and this infers that the active surface phase of the catalyst during the test also was Fe-oxide, rather than Fe-carbide. The results show that iron-based materials are potential candidates for application in a pyrolysis gas pre-conditioning step before further treatment or use, and a way of generating a hydrogen-enriched gas without the need for bio-crude condensation.